A study of the attractiveness on Islamic pawnbroking at Ar- Rahnu MAIDAM Kuala Terengganu / Najdah Abd Aziz … [et al.] - Abd Aziz, Najdah (2015)
Islamic pawnbroking or ar-Rahnu is based on shariah compliant, combined of four basic concepts, i.e. al-qardhul hassan (loan without interest), al-wadiah yad dhamanah (keeping valuable goods by guarantee), al-ujrah (storage fees) and ar-rahn (collateral) to make it as different with the conventional. From the Islamic perspective, the pawning contract is a voluntary charitable contract (tabarru’) whereby the pawned object is given without any financial compensation. In Malaysia, people more prefer Islamic pawnbroking rather than conventional one. Pawnbroking is very famous among the low income group and who need money urgently with condition that they need to pledge their valuable item in order to get the loan. The aim of this study is to identify the most influential factor that attract customers to pawn at Ar-Rahnu Maidam. There are some of identifiable variable from previous study which concerning convenient, quick cash, syariah compliant and staff attitude in measuring the attractiveness of Islamic pawnbroking at Ar-Rahnu MAIDAM, Terengganu, Malaysia. In conducting this study, 291 sets of questionnaire were distributed to the customers but only 205 sets of questionnaire were returned to the researcher. The result from the study showed all the variable give strong and significantly correlated with the attractiveness of Islamic pawnbroking.